Efektivitas Pengadaan Barang dan Jasa Melalui E-Catalogue di Kecamatan Kebayoran Lama Kota Administrasi Jakarta Selatan - Deby Ariesta (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2021)
This study aims to determine the effectiveness of E-Catalog procurement of goods and services in Kebayoran Lama District, South Jakarta Administration City, DKI Jakarta Province. This study uses a descriptive method with a qualitative approach. Data collection techniques were carried out through in-depth interview studies, observation, and documentation, during data collection techniques, data reduction, data display, and verification. This study indicates that the effectiveness of the procurement of goods and services of E-Catalogue has shown success, although it has not run optimally in its application, where efficiency and effectiveness are obtained in the indicators. From the aspect of time, the process of procuring goods and services for E-Catalogue is faster because it takes 1 week at most 3 weeks, conventionally it takes more than 4 weeks. in improving the performance of the number of procurement through E-Catalogue, the procurement process has not yet supported the SOP (Standard Operating System) to carry out an overall transformation, especially in relation to constraints in the electronic procurement system, having certification of procurement of goods and services in operation Computers need the assistance of other human resources to assist their implementation, due to the lack of ability to operate computers and the program and the participation of agencies in conducting the process of procuring goods and services electronically, they are not yet aware of the importance of carrying out the procurement process goods and services that are effective and efficient, the lesson that can be learned from this research is a strong commitment from the leadership to the staff as executor in the field.